Spring Boot Essentials - Speake, Matthew (Packt Publishing, 2021)
Leverage the rich Spring ecosystem to create complex and secure applications with Spring Boot About This Video Create and publish Spring Boot projects Examine existing Spring Boot projects and troubleshoot issues Create projects out of various technologies using starter dependencies In Detail Spring Boot provides some impressive features to simplify writing your code, and does so with minimal effort. It is the fastest way to get a Spring application up and running with the fewest lines of code and the least configuration. It aims to make development easy so that you can create production-grade applications and services. This course begins by helping you configure Spring Boot, then shows you a practical implementation of its various features. Then, you will work on running and debugging Spring Boot apps in the IDE. Following that, you'll learn the foundations of the Spring Boot platform and understand its operations. Afterwards, you'll understand layered architecture basics and how Spring Boot lets us create layered applications built on top of Spring. You'll also see how autoconfiguration works and understand how to use it and troubleshoot it where required. Finally, you'll be injecting properties into Spring-managed beans and publishing Spring events to ApplicationListeners. By the end of the course, you will get hands-on knowledge of running and debugging Spring Boot applications in the IDE. You will also be able to publish these applications on a website.